2012
DOI: 10.1111/cch.12002
|View full text |Cite
|
Sign up to set email alerts
|

Verbal definitions of familiar objects in blind children reflect their peculiar perceptual experience

Abstract: The results are discussed in line with embodied views of cognition that postulate mandatory perceptuomotor processing of words during access to their meaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This bias was observed irrespective of whether these blind children were aged 3to-6 or 6-to-8 years, and whether or not they received partial information without geometrical or texture cues or full information systematically containing geometrical cues, and occasionally texture cues. It should be noted that the same type of bias was obtained when blind children were asked to verbally define familiar objects, as compared to agematched sighted children (Vinter et al, 2013). Furthermore, in the blind children, the decrease in exploration times was associated with both a more organized exploration phase (indicated by a more frequent use of bimanual and symmetrical movements) and a better production of correct naming responses.…”
Section: Discussionmentioning
confidence: 65%
“…This bias was observed irrespective of whether these blind children were aged 3to-6 or 6-to-8 years, and whether or not they received partial information without geometrical or texture cues or full information systematically containing geometrical cues, and occasionally texture cues. It should be noted that the same type of bias was obtained when blind children were asked to verbally define familiar objects, as compared to agematched sighted children (Vinter et al, 2013). Furthermore, in the blind children, the decrease in exploration times was associated with both a more organized exploration phase (indicated by a more frequent use of bimanual and symmetrical movements) and a better production of correct naming responses.…”
Section: Discussionmentioning
confidence: 65%
“…With regards to the lexical component, Vinter and colleagues [75] showed that blind children tended to define words denoting concrete animate or inanimate familiar objects evoking their close perceptual experiences of touch, taste, and smell. It was different from what sighted children, who relied their definition on visual perception, and produced more visually oriented verbalism.…”
Section: Language and Communication Skillsmentioning
confidence: 99%
“…Like children with ASD, blind children may ask many questions, sometimes inappropriately, and may make 'off-the-wall' comments [83]. They also tend to refer more often to their personal experiences than sighted children when evoking familiar objects [75]. Mothers of children who present severe peripheral VI seem to take more frequent and longer turns at speaking or with other forms of communication than do mothers of sighted children, resulting in an asymmetry between relative dyads' experiences [67,85].…”
Section: Language and Communication Skillsmentioning
confidence: 99%
“…Moreover, other studies examining the language of the blind identified the use of multisensory references (mainly tactile and auditory) in the description of concepts and in the narration of mental images by these subjects (Anderson, & Olson, 1981;Lambert 2003;Vinter, Fernandes, Orlandi, & Morgan, 2013). These discoveries are linked with theories of embo-died cognition in the field of linguistics (Barsalou, 1999;Glenberg, & Kaschak, 2002).…”
Section: Verbal Description Of the Sensorial Experiencementioning
confidence: 97%